2014
DOI: 10.1136/jnnp-2014-308094
|View full text |Cite
|
Sign up to set email alerts
|

Aβ imaging with 18F-florbetaben in prodromal Alzheimer's disease: a prospective outcome study

Abstract: NCT01138111.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 36 publications
5
72
2
Order By: Relevance
“…However, potential subtle changes in Ab burden over time may not be apparent by visual inspection of the images. Thus, quantitative analysis has been found necessary for longitudinal observational studies and interventional trials when a change in amyloid burden measured by PET serves as a treatment endpoint (4,5).…”
mentioning
confidence: 99%
“…However, potential subtle changes in Ab burden over time may not be apparent by visual inspection of the images. Thus, quantitative analysis has been found necessary for longitudinal observational studies and interventional trials when a change in amyloid burden measured by PET serves as a treatment endpoint (4,5).…”
mentioning
confidence: 99%
“…44 Some studies satisfied both NINCDS-ADRDA and DSM-IV criteria, 22,23,[26][27][28]31,38 and others used only one set of criteria. Some studies that used NINCDS-ADRDA criteria adopted probable AD, 10,12,14,17,[19][20][21]23,[26][27][28][29]32,33 whereas other studies did not indicate the diagnosis as probable or possible AD. Our study excluded other types of dementia, not AD.…”
Section: Discussionmentioning
confidence: 99%
“…3,17,19,27,[29][30][31][32]43 Two studies included in this meta-analysis assessed hippocampus volume by MRI and amyloid burden by PET in the same patients. 29,32 These studies reported higher odds ratios/positive predictive value/negative predictive value/accuracy for amyloid PET than MRI hippocampus volume reduction on MRI. Another European collaborative study predicted conversion to AD in patients with MCI using CSF Aβ42 concentration, cortical metabolism by FDG-PET, and MRI hippocampus atrophy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that accumulation of Aβ plateaus while hippocampal volume continues to decrease. Therefore, over time, hippocampal atrophy and not accumulation of Aβ facilitates dementia progression [44].…”
Section: [ 18 F]-av-1 or [F-18]-bay94-9172 Or Florbetabenmentioning
confidence: 99%